2021
DOI: 10.47963/jobed.v9i.178
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border E-commerce Trade between China and Africa: Review of the Literature

Abstract: This article explores the opportunities, challenges, as well as the activities of the Chinese governmental and commercial stakeholders to promote cross-border e-commerce trade between China and Africa, based on the classification and correlation analysis of the literature from 2011 to 2019. The results show that the biggest driver for the development of China-Africa cross-border e-commerce trade is the gap between the rapid growth of the African population, especially the middle class, and the limited local ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…When due to the outbreak of COVID-19, travel restrictions from both Chinese and Mozambican sides caused them to be unable to continue their regular in-person trips to China (see also, Cissé, 2021; Mathews, 2022; Skovgaard-Smith, 2021), many of the traders quickly resorted to pursue their negotiations online instead. Chinese e-commerce platforms, such as Alibaba, have been aggressively expanding into African countries for some years now, and other cross-border business-to-business platforms, such as Chinagoods and e-Cantonfair, have been boosted recently (Li and Bode, 2020; Wu, 2020). Nevertheless, in 2021, Chinese–Mozambican trade mainly took place via WhatsApp and its Chinese equivalent WeChat.…”
Section: Switching and Bridging: Whatsapp In Chinese–mozambican Tradementioning
confidence: 99%
“…When due to the outbreak of COVID-19, travel restrictions from both Chinese and Mozambican sides caused them to be unable to continue their regular in-person trips to China (see also, Cissé, 2021; Mathews, 2022; Skovgaard-Smith, 2021), many of the traders quickly resorted to pursue their negotiations online instead. Chinese e-commerce platforms, such as Alibaba, have been aggressively expanding into African countries for some years now, and other cross-border business-to-business platforms, such as Chinagoods and e-Cantonfair, have been boosted recently (Li and Bode, 2020; Wu, 2020). Nevertheless, in 2021, Chinese–Mozambican trade mainly took place via WhatsApp and its Chinese equivalent WeChat.…”
Section: Switching and Bridging: Whatsapp In Chinese–mozambican Tradementioning
confidence: 99%
“…Several Systematic Literature Review (SLR) studies and Bibliometric Analyses which involve the examination of multiple studies have included zero literature on CBE that has based, focused or highlighted issues in Africa (Buldeo et al, 2023;Ding, Huo, and Campos, 2017;Zeng et al, 2017). Li and Bode (2020) conducted a study identified as an SLR which looked at CBE between Africa and China, the study involved 55 documents, most of which are not scientific studies or peerreviewed documents. Other studies on CBE focused or shed light on Africa, include: Brusick (2018); Han, Ma, Addo, Liao, and Fang, (2023);Makoza, 2023;Nuruzzaman, and Weber, (2021) The key contributions of this study are: One, the study provides direction on what can be done to support CBE in Tanzania and Africa in general.…”
Section: Introductionmentioning
confidence: 99%
“… The internet has many practical discussions over the extent to which Alibaba can be trusted by buyers (e.g., China Checkup, 2018), with commentators advising considerable caution. A range of other Chinese e‐commerce companies are also working to establish secure payment and delivery for African consumers (Li & Bode, 2020, pp. 51–52).…”
mentioning
confidence: 99%